Morphea Profunda with Tertiary Lymphoid Follicles: Description of Two Cases and Review of the Literature - Angelo Cassisa; Margherita Vannucchi (MDPI AG, 2022)
Morphea profunda or subcutaneous (deep) morphea is a variant of localized morphea, characterized by one or more ill-defined, deep sclerotic plaque. Preferential sites are the abdomen, trunk, sacral area, or extremities. The presence of hyperplastic lymphoid follicles in the context of the sclerotic bands of morphea is rarely described. Localized scleroderma is sustained by a profibrotic inflammatory profile. Transforming growth factor-β (TGF-β), an imbalance between functional subclasses of T-lymphocytes (innate immune cells) has a role in activate collagen deposition. In this case report, we present two cases of morphea profunda with lymphoid follicular hyperplasia. A systematic review of the literature on the pathophysiology of localized scleroderma is also presented, with particular reference to the presence of lymphoid structures.